An Unusual Case of Cystic Fibrosis Associated Pneumocystis jiroveci Pneumonia in an Infant. (13th December 2016) - Kaur, Ravinder; Katariya, Priyanka; Dhakad, Megh Singh; Mehra, Bhanu; Jhamb, Urmila; Dubey, A. P.
Abstract : Pneumocystis jiroveci pneumonia (PJP) is one of the major infections in patients with impaired immunity. The entity is common in HIV-seropositive individuals but quite very rare in HIV-seronegative individuals especially children. We report here a case of 16-week-old HIV-seronegative infant with chief complaint of chronic cough of one month of evolution. Sweat chloride test for diagnosis of cystic fibrosis was positive. Bronchoalveolar lavage (BAL) fluid was collected and Pseudomonas aeruginosa was isolated on culture. Empirical antibiotic regimen comprising ceftriaxone and azithromycin was initiated that was switched to meropenem as per antimicrobial susceptibility report, but the patient did not improve. Subsequently, an immunofluorescence staining of BAL fluid was performed and P. jiroveci cysts were detected. Following a laboratory confirmation of Pneumocystis pneumonia, cotrimoxazole was added and the clinical condition of the patient significantly improved. This is an unusual case wherein unsuspected PJP occurred and since signs and symptoms of the patient persisted even after the initiation of antimicrobial therapy for Pseudomonas infection and resolved only after treatment for PJP was started, it suggests a causative role of P. jiroveci rather than colonization/contamination.